FETAL MUMMIFICATION AMONG A QUADRUPLET IN KANNI ADU DOE - S. Alagar; S. Satheshkumar; S. Raja; S. Prakash (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A case of fetal mummification among one of the quadruplet kids was reported in a fourth parity Kanni adu doe.